2016
DOI: 10.1007/s11999-016-4709-3
|View full text |Cite
|
Sign up to set email alerts
|

Addition of a Medial Locking Plate to an In Situ Lateral Locking Plate Results in Healing of Distal Femoral Nonunions

Abstract: Background Nonunion of the distal femur after lateral plating is associated with axial malalignment, chronic pain, loss of ambulatory function, and decreased knee ROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 19 publications
(35 reference statements)
1
38
0
1
Order By: Relevance
“…Holzman et al reported that the complication rate in their study was 30% which is higher than the findings of the present study where we found complication rate was 20% of the cases. 7 Just the findings of the present study, this study also reported a very good union rate but slightly more rate of complications.…”
Section: Discussionsupporting
confidence: 80%
“…Holzman et al reported that the complication rate in their study was 30% which is higher than the findings of the present study where we found complication rate was 20% of the cases. 7 Just the findings of the present study, this study also reported a very good union rate but slightly more rate of complications.…”
Section: Discussionsupporting
confidence: 80%
“…Nine studies reported outcomes of case series with double plating of femoral non-unions including the proximal femur, femoral shaft and distal femur [4,24,[39][40][41][42][43][44][45]. Pydisetty et al [42] analysed 10 patients with revision surgery for non-union of bisphosphonate-related subtrochanteric fractures.…”
Section: Non-union Of the Femurmentioning
confidence: 99%
“…It is de ned as good when the both conditions can be reached, accept when one condition can be reached and poor with none condition can be reached. The imaging standard of fracture union 17 was de ned as the blur of fracture line on the X-ray plain lm, and the continuous callus passing through at least three cortical bone of the fracture site. The implant failure 18 de ned as that: lag screw cut out, coxa vara (The caput-collum-diaphysis angle less than 5°above the contralateral hip) or nonunion, implant broken, periprosthetic fracture without high energy damage.…”
Section: Data Collectionmentioning
confidence: 99%